Capital game: male athletes` rationalisation of playing hurt and reproduction of the risk, pain, and injury custom in professional combat sports - Ryou, J.; Lee, E. (Qualitative Research in Sport, Exercise and Health, 2023)
As the phenomenon of playing hurt persists in sports, extant literature has explored the risk, pain, and injury custom (RPIC) from diverse angles. However, academic endeavours revealing the agency-structure continuum between individual agents` willingness to play hurt and the capital structure related to the RPIC remain limited. This study aims to investigate professional athletes` health-compromising practice and its underlying mechanism through capital games. Drawing on Bourdieu`s theory of practice, we examined two research questions: (a) how does individual athletes` desire for capital justify playing hurt? and (b) how are their capital games connected to the RPIC? Empirical data were collected through semi-structured and photo-elicitation interviews with eight athletes and six coaches (ex-athletes) from three combat sports. The data were interpreted using reflexive thematic analysis. The findings were categorised into two narratives: (a) rationalisation of playing hurt and (b) reproduction of the RPIC. First, our participants continued playing hurt, expecting certain rewards (cultural, social, economic, and performance capital); this profit-seeking aspiration rationalised self-destructive action as an investment to garner social energy in the field. Second, the more athletes immersed themselves in capital games using health as a token, the more prominent the habitus of playing hurt became in the field. This RPIC reproduction mechanism drove former/present athletes` choices to converge into an identical career trajectory, uni-taste, and limited subversion strategy, trapping them in a cycle where the victim becomes another perpetrator of playing hurt. These results are expected to provide sport institutions with insights into building safer sporting environments.